Phosphorylation of the Kinase Interaction Motif in Mitogen-activated Protein (MAP) Kinase Phosphatase-4 Mediates Cross-talk between Protein Kinase A and MAP Kinase Signaling Pathways - Dickinson, Robin J. (American Society for Biochemistry and Molecular Biology, 2011)
MAP kinase phosphatase 4 (DUSP9/MKP-4) plays an essential role during placental development and is one of a subfamily of three closely related cytoplasmic dual-specificity MAPK phosphatases, which includes the ERK-specific enzymes DUSP6/MKP-3 and DUSP7/MKP-X. However, unlike DUSP6/MKP-3, DUSP9/MKP-4 also inactivates the p38α MAP kinase both in vitro and in vivo. Here we demonstrate that inactivation of both ERK1/2 and p38α by DUSP9/MKP-4 is mediated by a conserved arginine-rich kinase interaction motif located within the amino-terminal non-catalytic domain of the protein. Furthermore, DUSP9/MKP-4 is unique among these cytoplasmic MKPs in containing a conserved PKA consensus phosphorylation site (55)RRXSer-58 immediately adjacent to the kinase interaction motif. DUSP9/MKP-4 is phosphorylated on Ser-58 by PKA in vitro, and phosphorylation abrogates the binding of DUSP9/MKP-4 to both ERK2 and p38α MAP kinases. In addition, although mutation of Ser-58 to either alanine or glutamic acid does not affect the intrinsic catalytic activity of DUSP9/MKP-4, phospho-mimetic (Ser-58 to Glu) substitution inhibits both the interaction of DUSP9/MKP-4 with ERK2 and p38α in vivo and its ability to dephosphorylate and inactivate these MAP kinases. Finally, the use of a phospho-specific antibody demonstrates that endogenous DUSP9/MKP-4 is phosphorylated on Ser-58 in response to the PKA agonist forskolin and is also modified in placental tissue. We conclude that DUSP9/MKP-4 is a bona fide target of PKA signaling and that attenuation of DUSP9/MKP-4 function can mediate cross-talk between the PKA pathway and MAPK signaling through both ERK1/2 and p38α in vivo.